Wang Lungs Struggle for Wealth in Pearl S. Buck The Good Earth - HUDAN AJI SUBEKTI (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2019)
Abstract This thesis is concentrated on the struggle of Wang Lung for their life to reach wealth as the main character in the novel entitled The Good Earth. The purpose of this thesis is written is to reveal the process of Lung to be rich. How Lung can get rich and what is the factor for Lung who has to be rich are the questioner of this thesis. Lung not only work well, but he also changes his life while he gets a suffering moment. This suffering moment is one factor that Lung gets from external caused. However, Lung gets a depressed moment between internal and external. Those are factors that Lung gets the motivation to be undergone and passed it in order to can reach a wealth. Keywords: Struggle, motivation, development for the wealth process. Abstrak Skripsi ini fokus terhadap perjuangan Wang Lung terhadap hidupnya untuk menempuh kekayaan yang merupakan tokoh utama di dalam sebuah novel yang bejudul The Good Earth. Tujuan penulisan skripsi ini adalah untuk mengemukakan sebuah proses dari Wang Lung untuk menempuh kekayaan. Bagaimana Wang Lung menjadi kaya dan Apa sebabnya Lung harus menjadi kaya adalah pertanyaan penelitian dari skripsi ini. Lung tidak hanya bekerja dengan baik, tetapi dia juga harus mengubah hidupnya ketika mengalami masa-masa terpuruk. Keadaan ini adalah salah satu faktor yanf Lung dapatkan dari faktor eksternal. Bagaimanapun Lung mendapatkan tekanan dari internal dan eksternal. Semua itu adalah faktor dimana Lung mendapatkan motivasi dan melewatinya agar dapat mencapai kekayaan. Keywords: Perjuangan, Motivasi, Proses perkembangan dan Kekayaan.